Textual analysis of social movements in the State of Pernambuco: a study of behavioral patterns (Research, Society and Development, 2021)
Social movements and manifestations in Brazil are quite dynamic, however, the studies that deal with these events have not always followed this dynamism and evolution. Due to globalization and the speed in the spreading of information, and disinformation, through the advent of digital communications, social movements and manifestations in Brazil, in line with Latin America, have the same trend of diversification and complexity. Not differently, the studies carried out about social movements in the state of Pernambuco are fruits of a very heterogeneous political conjuncture and that, historically, have particularities due to their historical/social conjuncture. In view of this heterogeneity, new proposals of behavioral analysis about the motivations that permeate the social movements in the state of Pernambuco aim at understanding the behaviors originating from these movements from a perspective that goes beyond the hegemony of the social sciences, using Artificial Intelligence. This scientific research aims to identify, as well as, analyze the behavior patterns of social movements in the state of Pernambuco, obtaining an understanding about these new configurations of organized civil society, explaining the multiple types of preventive actions that can be taken to avoid conflicts and mitigate risks. From this understanding, we seek to explore the analysis of risks with a tendency towards police confrontations, as well as, to explore the diversity of employment of military police troops in social movements in the state of Pernambuco.